2002
DOI: 10.1136/sti.78.5.349
|View full text |Cite
|
Sign up to set email alerts
|

News from the frontline: sexually transmitted infections in teenagers attending a genitourinary clinic in south east London

Abstract: Objectives: To define the incidence and characterise the clinical presentation of sexually transmitted infections (STI) in people aged <16 years old attending a genitourinary clinic in south east London. Methods: Cross sectional analysis of clients aged <16 years attending one genitourinary clinic. A subgroup was identified for priority treatment. Data collected included age, reason for presentation, diagnosis, contraceptive use, and adherence to therapy. Diagnoses were compared to the KC60 codes for female at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…However, the authors did not report on the number of girls who were sexually assaulted/raped in their study. 13 Our study showed that the overall prevalence of STIs in female child and adolescent survivors of rape and sexual assault attending a specialist GUM clinic was high. Chlamydial infection was significantly more common in post-pubertal girls who were involved in consensual sexual activity before the index assault.…”
Section: Discussionmentioning
confidence: 59%
“…However, the authors did not report on the number of girls who were sexually assaulted/raped in their study. 13 Our study showed that the overall prevalence of STIs in female child and adolescent survivors of rape and sexual assault attending a specialist GUM clinic was high. Chlamydial infection was significantly more common in post-pubertal girls who were involved in consensual sexual activity before the index assault.…”
Section: Discussionmentioning
confidence: 59%
“…18 One exception was a study in racially diverse adolescents, which reported a significant fall in vaginal pH as gynaecological age increased. 19 Vaginal pH could account for increased risk of BV in less mature adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…17 A study of under 16s attending a GUM clinic in London found that 19% of all female attendees were pregnant, and 76% of those who were not pregnant were not using any contraception at the time. 18 Over half of these women reported that they did not receive advice on contraception during their visit.…”
Section: Logisticsmentioning
confidence: 99%